2019
DOI: 10.1111/eea.12804
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of a carabid beetle in farmland is driven by habitat‐specific motility and preference at habitat interfaces

Abstract: Carabid beetles are common predators of pest insects and weed seeds in agricultural systems. Understanding their dispersal across farmland is important for designing farms and landscapes that support pest and weed biological control. Little is known, however, about the effect of farmland habitat discontinuities on dispersal behaviour and the resulting redistribution of these beetles. We released 1,985 well‐fed and 1,680 food‐deprived individuals of the predatory carabid beetle Pterostichus melanarius (Illiger)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…Such ecotones can reduce migration, change the daily and seasonal movements of insects. An increase in the species diversity of insects adjacent to the biotope forest is the most likely result [41][42][43]. This is exactly what was obtained in our conditions.…”
Section: Resultssupporting
confidence: 88%
“…Such ecotones can reduce migration, change the daily and seasonal movements of insects. An increase in the species diversity of insects adjacent to the biotope forest is the most likely result [41][42][43]. This is exactly what was obtained in our conditions.…”
Section: Resultssupporting
confidence: 88%
“…Only the Pterostichus ground beetle was found to be more abundant in the REF system. Although contradictory to Thomas et al (2006) who found Pterostichus to prefer less dense crop stands, our finding is in line with Allema et al (2019) who showed that Pterostichus preferentially occupy large-scale cereal monocultures.…”
Section: Natural Enemies Of Aphids In Wheatsupporting
confidence: 55%
“…For example, for NEs we looked only at abundance and not at community composition at the species level. In doing so we could have missed potential treatment effects, as it has been shown for instance that certain ground beetle species prefer particular crops and crop arrangements over others (Allema et al 2015;Allema et al 2019). With both NEs and weeds, species richness is of interest from the perspective of biodiversity preservation, but species composition also matters in regard to AES delivery when the presence of certain species or functional groups may be more predictive of associated effects (Bàrberi et al 2018;Dassou and Tixier 2016).…”
Section: Prospects For Strip and Pixel Croppingmentioning
confidence: 99%
“…However, in some cases higher abundances were found in conventional systems (Baguette and Hance, 1997;Hatten et al, 2007;Menalled et al, 2007), but this was usually due to a single dominant species that was either indifferent to disturbance or resilient to it thanks to good colonization capabilities (Baguette and Hance, 1997;Hatten et al, 2007). Allema et al (2019) also hypothesized that in disturbed open habitat, such as conventional fields, carabids exhibit a more intense foraging activity than in complex habitat, resulting in increased trapping efficacy rather than increased abundance.…”
Section: Influence Of Soil Management On Natural Enemy Abundance and ...mentioning
confidence: 99%